Comparison of Clinical and Radiographic Success between MTA and Biodentine in Pulpotomy of Primary Mandibular Second Molars with Irreversible Pulpitis: A Randomized Double-Blind Clinical Trial - Alireza Eshghi; Maryam Hajiahmadi; Mohammad Hossein Nikbakht; Mona Esmaeili (International Journal of Dentistry)
Introduction. Among the new therapeutic materials, MTA and Biodentine are recommended for pulpotomy and sealing the pulp. Considering the similar characteristics of these two materials and considering that their effects on the treatment of primary second molars with irreversible pulpitis have not been compared properly, this study aimed to compare clinical and radiographic success between MTA and Biodentine in pulpotomy of primary mandibular second molars with irreversible pulpitis. Materials and Methods. This study was conducted as a randomized double-blind clinical trial. Participants were selected according to inclusion criteria and 52 samples were randomly selected using random numbers table in group A. Then, patients in the next group B were matched with the first group in terms of age range and sex. In group A, the remaining pulp was covered with 2 mm MTA+ and in group B with 3 mm Biodentine. Participants were called for clinical evaluation every three months for 12 months (long-term follow-up). Radiographic evaluations were in the sixth and twelfth months. Results. Fischer’s exact test showed that there was no significant difference between MTA and Biodentine in terms of clinical and radiographic success rates (P value = 1). According to the results of the Kaplan–Meier test, the survival rate in both pulp treatment methods was similar in symptomatic teeth. Conclusions. The results of this study showed that Biodentine properties are similar to MTA, and both materials show high clinical and radiographic success rates in long-term follow-up.